(untitled) (UNED Research Journal, 2018)
The elaboration of written tests requires a series of steps that determine the quality of the final product. We surveyed 33 teachers in a Costa Rican distance university and found that most complain of insufficient time given to elaborate tests. Not all teachers elaborate an item specification chart or discuss their work with their bosses, who provide the format and objectives. Nevertheless, all teachers check course contents before designing the exam. Teachers should be given more time and supervision to prepare tests.